ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015 - 2017 - Noor Khasanah, 16.05.62.0026; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
The porpose of this research is to know the influence of firm size, profitability, asset structure and liquidity to the capital structure. The dependent variabel in this study is the capital structure, as for the independent variables in this study are firm size, profitability, asset structure, and liquidity. Based on criteria which has been decided, it wash selection 40 companies from 61 firm property and real estate listed on the Indonesian Stock Excgange for the periode of 2015 to 2017. The sampling technique was chose by purposive sampling. The method of analysis used in this study is multiple linear regression. The reasule of this research showed that firm size and liquidity has significant to the capital structur, profitability and asset structure has insignificant to the capital structure.